Target-capture full-length double-stranded cDNA long-read sequencing through Nanopore revealed novel intron retention in patient with tuberous sclerosis complex - Ura, Hiroki; Togi, Sumihito; Niida, Yo (Frontiers in Genetics, 2023)
Tuberous sclerosis complex (TSC) is a relatively common autosomal dominant disorder characterized by multiple dysplastic organ lesions and neuropsychiatric symptoms caused by loss-of-function mutation of either TSC1 or TSC2. The genetic diagnosis of inherited diseases, including TSC, in the clinical field is widespread using next-generation sequencing. The mutations in protein-coding exon tend to be verified because mutations directly cause abnormal protein. However, it is relatively difficult to verify mutations in the intron region because it is required to investigate whether the intron mutations affect the abnormal splicing of transcripts. In this study, we developed a target-capture full-length double-stranded cDNA sequencing method using Nanopore long-read sequencer (Nanopore long-read target sequencing). This method revealed the occurrence of intron mutation in the TSC2 gene and found that the intron mutation produces novel intron retention splicing transcripts that generate truncated proteins. The protein-coding transcripts were decreased due to the expression of the novel intron retention transcripts, which caused TSC in patients with the intron mutation. Our results indicate that Nanopore long-read target sequencing is useful for the detection of mutations and confers information on the full-length alternative splicing of transcripts for genetic diagnosis.